Ohmic contact formation to β-Ga2O3 nanosheet transistors with Ar-containing plasma treatment - Chen, Jinxin (2024)
Effective Ohmic contact between metals and their conductive channels is a crucial step in developing high-performance Ga2O3-based transistors. Distinct from bulk materials, excess thermal energy of the annealing process can destroy the low-dimensional material itself. Given the thermal budget concern, a feasible and moderate solution (i.e., Ar-containing plasma treatment) is proposed to achieve effective Ohmic junctions with (100) β-Ga2O3 nanosheets. The impact of four kinds of plasma treatments (i.e., gas mixtures SF6/Ar, SF6/O2/Ar, SF6/O2, and Ar) on (100) β-Ga2O3 crystals is comparatively studied by X-ray photoemission spectroscopy for the first time. With the optimal plasma pre-treatment (i.e., Ar plasma, 100 W, 60 s), the resulting β-Ga2O3 nanosheet field-effect transistors (FETs) show effective Ohmic contact (i.e., contact resistance RC of 104 Ω·mm) without any post-annealing, which leads to competitive device performance such as a high current on/off ratio (>107), a low subthreshold swing (SS, 249 mV/dec), and acceptable field-effect mobility ((Formula presented.), ~21.73 cm2 V−1 s−1). By using heavily doped β-Ga2O3 crystals (Ne, ~1020 cm−3) for Ar plasma treatments, the contact resistance RC can be further decreased to 5.2 Ω·mm. This work opens up new opportunities to enhance the Ohmic contact performance of low-dimensional Ga2O3-based transistors and can further benefit other oxide-based nanodevices.